Vitamin D Status and SARS-CoV-2 Infection and COVID-19 Clinical Outcomes - Chiodini, Iacopo; Gatti, Davide; Soranna, Davide; Merlotti, Daniela; Mingiano, Christian; Fassio, Angelo; Adami, Giovanni; Falchetti, Alberto; Eller-Vainicher, Cristina; Rossini, Maurizio; Persani, Luca; Zambon, Antonella; et al. (Frontiers in Public Health, 2021)
Background: Several studies suggest an association between serum 25-hydroxyvitamin D (25OHD) and the outcomes of Severe Acute Respiratory Syndrome Corona-Virus-2 (SARS-CoV-2) infection, in particular Coronavirus Disease-2019 (COVID-19) related severity and mortality. The aim of the present meta-analysis was to investigate whether vitamin D status is associated with the COVID-19 severity, defined as ARDS requiring admission to intensive care unit (ICU) or mortality (primary endpoints) and with the susceptibility to SARS-CoV-2 and COVID-19-related hospitalization (secondary endpoints). Methods: A search in PubMed, ScienceDirect, Web of Science, Google Scholar, Scopus, and preprints repositories was performed until March 31th 2021 to identify all original observational studies reporting association measures, or enough data to calculate them, between Vitamin D status (insufficiency <75, deficiency <50, or severe deficiency <25 nmol/L) and risk of SARS-CoV-2 infection, COVID-19 hospitalization, ICU admission, or death during COVID-19 hospitalization. Findings: Fifty-four studies (49 as fully-printed and 5 as pre-print publications) were included for a total of 1,403,715 individuals. The association between vitamin D status and SARS-CoV2 infection, COVID-19 related hospitalization, COVID-19 related ICU admission, and COVID-19 related mortality was reported in 17, 9, 27, and 35 studies, respectively. Severe deficiency, deficiency and insufficiency of vitamin D were all associated with ICU admission (odds ratio [OR], 95% confidence intervals [95%CIs]: 2.63, 1.45–4.77; 2.16, 1.43–3.26; 2.83, 1.74–4.61, respectively), mortality (OR, 95%CIs: 2.60, 1.93–3.49; 1.84, 1.26–2.69; 4.15, 1.76–9.77, respectively), SARS-CoV-2 infection (OR, 95%CIs: 1.68, 1.32–2.13; 1.83, 1.43–2.33; 1.49, 1.16–1.91, respectively) and COVID-19 hospitalization (OR, 95%CIs 2.51, 1.63–3.85; 2.38, 1.56–3.63; 1.82, 1.43–2.33). Considering specific subgroups (i.e., Caucasian patients, high quality studies, and studies reporting adjusted association estimates) the results of primary endpoints did not change. Interpretations: Patients with low vitamin D levels present an increased risk of ARDS requiring admission to intensive care unit (ICU) or mortality due to SARS-CoV-2 infection and a higher susceptibility to SARS-CoV-2 infection and related hospitalization.